The odious Haitian independence debt - Kim Oosterlinck; Ugo Panizza; W. Mark C. Weidemaier; Mitu Gulati (Graduate Institute of International and Development Studies, 2021)
This article introduces the Haitian Independence Debt of 1825 to the odious debt and sovereign debt literatures. We argue that the legal doctrine of odious debt is surprisingly and perhaps indefensibly narrow possibly because of historical contingency rather than any underlying logic or principle. The story of the Haitian Independence Debt of 1825 serves as an illustrative case study. In the context of telling that story, we provide estimates of the evolution of Haiti's external debt-to-GDP ratio over 1825-2020, and discuss the implications of the independence debt for the economy of Haiti. We conclude by discussing the implications of Haiti's Independence Debt for the doctrine of odious debt and the possibilities for Haiti to recover compensation.
Keywords: G15; H63; K34; O54; 330; Haiti; Odious Debt; Debt and Growth